Biplanar EOS screening in children with hereditary multiple osteochondromas: a feasible screening method? - Hedelin, Henrik; Ahlin, Jenny; Danielsson, Aina; Brisby, Helena; Lagerstrand, Kerstin (Frontiers in Pediatrics, 2026)
BackgroundChildren with Hereditary Multiple Ostechondromas (HMO) require regular screening to identify gradual dysplasia or osteochondromas that need surgery. EOS biplanar imaging enables interpretation of weight-bearing malalignment with low ionizing radiation exposure.ObjectiveTo determine whether EOS can be used as a screening method for presence of osteochondromas and frontal plane malalignment in the lower extremities in HMO children.MethodsPresence of ostechondromas was determined in the lower extremities in ten children [age: 14.5(10–20) years, six males] using EOS. Also, frontal plane malalignment was registered. Further, patient reported experience measures (PREM) were collected through a questionnaire. EOS findings were compared with conventional whole-leg radiographs. The frontal plane malalignment was determined using standardized measurements for hip, knee and ankle joints. Reproducibility for both modalities was determined through repeated measurements by the same observer.ResultsEOS systematically identified significantly more osteochondromas than conventional frontal radiographs in the lower limbs. Measurements of malalignment in the frontal plane showed only a small systematic bias with narrow limits of agreement between the modalities with mean difference −0.86 degrees (95% LOA: −6.36–4.63 degrees). Intra-observer agreement for both modalities was very good (CVradiographs = 2%; CVEOS = 1%;). The PREM findings showed that EOS was well-tolerated by the children.ConclusionsEOS biplanar imaging was well-tolerated and seemed to be a feasible alternative to conventional radiographs for screening of children with HMO, offering reduced radiation exposure and the potential to detect more osteochondromas in the lower limbs.